Konsumerisme Masyarakat Nelayan: Studi pada Komunitas Istri Nelayan Pulau Messah, Nusa Tenggara Timur - Mukhammad Fatkhullah; Fidarini Devi Widasari; Muhammad Alhada Fuadilah Habib (Universitas Islam Darul Ulum Lamongan, 2022)
The fishermen's wife community in Messah Island is known to be very consumptive. They spend most of their income on lifestyle even though they have not been able to meet their basic needs. This study seeks to see how consumptive behavior in the fishermen's wife community can be entrenched, as well as its various implications. The method used in this research is descriptive qualitative method. Data collection was carried out by in-depth interviews, while the informants were determined purposively. As a result, the consumerism of the fishermen's wife community in Messah Island is driven by internal and external factors. Internal factors that shape consumptive behavior refer to the high desire to be different from others and the low quality of human resources in managing assets and finances. Meanwhile, the external factors that shape consumptive behavior refer to the ease of access to consumer goods and credit, as well as the consumptive social environment. The consumptive lifestyle of the fishermen's wife community has implications for the practice of exploitation of natural and human resources, the low quality of life that is not comparable to the productivity of fishery products, and the confinement of fishing communities in a culture of poverty that forces them to be in the same condition.